HUBUNGAN ANTARA ASUPAN ENERGI, AKTIVITAS FISIK DAN KUALITAS TIDUR TERHADAP STATUS GIZI PADA SANTRI PUTRI PONDOK PESANTREN KYAI GALANG SEWU SEMARANG - Nur Eliska Aulia; Angga Hardiansyah; Widiastuti Widiastuti (Universitas Mitra Indonesia, 2022)
Nutrition and health problems in adulthood can occur in every individual, without exception young adults who live in Islamic Boarding Schools. Young adults need serious attention to nutritional problems because during this period there is a significant change in lifestyle so they are prone to changes in consumption patterns that cause energy imbalances in the body. The purpose of this study was to analyze the relationship between energy intake, physical activity and sleep quality with the nutritional status of female students at the Kyai Galang Sewu Islamic Boarding School, Semarang. This study used a cross-sectional study design. The sample in this study amounted to 74 students obtained by the Slovin formula using the simple random sampling method. Data were collected directly using a 3x24 hour food recall questionnaire, a 2x24 hour Physical Activity Level (PAL) questionnaire, a 1x24 hour Pitssburgh Sleep Quality Index (PSQI) questionnaire and anthropometric data measurements. Data analysis used gamma correlation test. The results showed that the majority of respondents were 21 years old (23%), the majority of the nutritional status was normal (73%), the majority of the energy intake was less (79,7%), the majority of the physical activity was light (97,3%) and the quality of sleep was low. the majority is bad (93,2%). Furthermore, the results of statistical tests of the relationship between energy intake and nutritional status (p = 0,566), the relationship between physical activity and nutritional status (p = 0,318) and the relationship between sleep quality and nutritional status (p = 0.,579). The conclusion of this research is no correlation between energy intake and the nutritional status of female students. There is no correlation between physical activity and the nutritional status of female students. And there is no correlation between sleep quality and nutritional status of female students. Masalah gizi dan kesehatan pada usia dewasa dapat terjadi pada setiap individu, tanpa terkecuali dewasa muda yang bertempat tinggal di pondok pesantren. Usia dewasa muda perlu mendapat perhatian yang serius akan masalah gizi karena pada masa tersebut terjadi perubahan pola hidup yang signifikan sehingga rawan terhadap perubahan pola konsumsi yang menyebabkan ketidakseimbangan energi dalam tubuh. Tujuan penelitian adalah untuk menganalisis hubungan asupan energi, aktivitas fisik dan kualitas tidur terhadap status gizi pada santri putri Pondok Pesantren Kyai Galang Sewu Semarang. Penelitian ini menggunakan desain cross-sectional study. Sampel dalam penelitian ini berjumlah 74 santri yang diperoleh dengan rumus Slovin menggunakan metode simple random sampling. Pengambilan data dilakukan secara langsung menggunakan kuesioner food recall 3x24 jam, kuesioner Physical Activity Level (PAL) 2x24 jam, kuesioner Pitssburgh Sleep Quality Index (PSQI) 1x24 jam dan pengukuran data antropometri. Analisis data menggunakan uji korelasi gamma. Hasil penelitian menunjukkan bahwa responden paling banyak berusia 21 tahun (23%), status gizi mayoritas normal (73%), asupan energi mayoritas kurang (79,7%), aktivitas fisik mayoritas ringan (97,3%) dan kualitas tidur mayoritas buruk (93,2%). Selanjutnya, hasil uji statistik hubungan antara asupan energi terhadap status gizi (p=0,566), hubungan antara aktivitas fisik terhadap status gizi (p=0,318) dan hubungan antara kualitas tidur terhadap status gizi (p=0,579). Kesimpulan dari penelitian ini adalah tidak terdapat hubungan antara asupan energi terhadap status gizi santri putri. Tidak terdapat hubungan antara aktivitas fisik terhadap status gizi santri putri. Dan tidak terdapat hubungan antara kualitas tidur terhadap status gizi santri putri.